A study on knowledge, attitude and practice (KAP) on HIV/AIDS amongst the employees of Telkom SA Ltd. - Kamaldien, Yusuf (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Industrial Psychology. School of HIV/AIDS Management))--University of Stellenbosch, 2009.